THE STORY OF JOSEPH IN THE GENESIS AND SURAH YUSUF - Baharuddin, Rahmawati (ULUL ALBAB Jurnal Studi Islam, 2009)
The beauty of Joseph's story has become a byword, long before the arrival of Islam. The Qur'an itself confirms that the story of Joseph is the best (ahsan al-qasas). The study of the Qur'anic text and the New Testament (Genesis 37-50) shows the similarity of the story of Joseph in outline, but also the differences in function and reasoning of the story. The first fact shows the similarity of religious and literary discourse between the Islamic and Jewish communities at the beginning of the coming of Islam, while the second shows the originality of the story of Yusuf in the Qur'an. In the New Testament the story of Joseph emphasizes the history of the journey of a nation, while the Qur'an describes the story of Joseph to strengthen the belief of the Prophet and his followers.